Boric compounds as food preservatives
1926-06 1926 1920s 8 pages - 8 - THE DOMESTIC LARDER. Convenience is rated at such a ridiculously high value nowadays that in the manufacture of foodstuffs the most serious consideration has to be given to saving the public the smallest amount of trouble. What the consumer desires is a permanent foodstuff which is always ready for consumption. If the manufacturer, tradesman and consumer are not allowed to use preservatives, it becomes more imperative to insist in all houses on the provision of a well-arranged larder - cool, airy, and easy to keep clean. Encouragement should also be given to facilitate in the summer the distribution of ice. Suggestions Arising out of this Memorandum on Boric Compounds in Foodstuffs. (1) A request should be made for the evidence given before the "Departmental Committee on the Use of Preservatives and Colouring Matters in Food" to be published. (2) An agreement should be made by the scientists of the world as to the conclusions to be drawn from what we at present know of the physiological action of boric compounds. (3) Further scientific research as to the physiological effects of boric compounds should be undertaken under National control. (4) Pending these results, the use of boric compounds in foodstuffs should be prohibited. 292/840/1/3